COVID-19, an opportunity to grow in humanity - Briozzo Pereyra, María Teresa (2020)
A brief introduction indicates the subject of study and at the same time points out the anthropological and ethical approach to it. When we go through critical moments in history, the best and also the worst found in man becomes evident. The COVID-19 pandemic also showed us this reality: humanity, solidarity, heroism, but also indifference, individualism.  A glance is made at the unexpected storm that is shaking humanity and a distracted humanity is perceived, trusting in its resources, and occupied in its interests, believing itself omnipotent. It has been observed how Pope Francis meets the crisis by giving guidance. Along with him, a series of authors have been found who reflect on the situation, exposing various aspects of the challenge of the current pandemic. At the same time, the need for a change in the human person is recognized; It is necessary for them to grow in humanity to recognize their vulnerability and to face tragic unforeseen events with dignity and solidarity. The resolution of the pandemic demonstrates the impact of the current economic and ideological system, based on consumerism, profit and individualism the need for a paradigm shift is highlighted; what we call normality is not the normality of a human life that uses the other and destroys their habitat. A short-sighted anthropological excess is recognized, leading to selfishness and ecological catastrophe.